2021
DOI: 10.1016/j.ijpharm.2020.120092
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of vitamin C in emulsions of liquid crystalline structures

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Our results revealed that the developed emulsions contained a complex colloidal structure in the oil‐water interface, consisting of the lamellar liquid crystalline (Lα) and lamellar gel crystalline (Lβ) phases. This structure was very efficient in preventing the oxidation of AA 15 . Liquid crystals were first described in emulsions in 1969.…”
Section: Introductionmentioning
confidence: 99%
“…Our results revealed that the developed emulsions contained a complex colloidal structure in the oil‐water interface, consisting of the lamellar liquid crystalline (Lα) and lamellar gel crystalline (Lβ) phases. This structure was very efficient in preventing the oxidation of AA 15 . Liquid crystals were first described in emulsions in 1969.…”
Section: Introductionmentioning
confidence: 99%
“…At the end of the analysis (60 days), the L‐AA content varied greatly between samples (<LOD to 79.97 mg L −1 ; Table 5). These results are notable owing to the unstable characteristics of L‐AA [43]. Besides, it was noted that between 0 and 15 days, and 45 and 60 days, the L‐AA concentration of AL1, AH3, AH4 and AH1 samples decreased at a slower rate than at other analysis times (Figure 2).…”
Section: Resultsmentioning
confidence: 95%
“…Although liquid crystals have been successfully applied for delivery of cosmetic ingredients, such as retinol, resveratrol, ascorbic acid [56,62,63], their application as a delivery system for peptides has not yet been as common as other lipid‐base delivery systems. Therefore, further investigations focusing on the liquid crystals containing anti‐wrinkle peptides are considerably required.…”
Section: Encapsulation Of Anti‐wrinkle Peptides Into Lipid‐based Nano...mentioning
confidence: 99%